Early Seizures during Stroke - Naydenov, Christiyan; Mancheva, Velina; Manchev, Lachezar; Yordanova, Antoaneta (Open Access Macedonian Journal of Medical Sciences, 2022)
INTRODUCTION: The connections between seizures and stroke, their characteristics and features are barely developed and also very important for the outcome. The diagnostic problem leads to ineffective treatment due to difficult selection of patients who are subject to prevention with antiepileptic drugs (AEDs) on one hand. On the other hand, is impossible to exam every stroke patient by EEG. We need an algorithm for screening indicated patients and conducting the EEG. After that we can include properly AED as a prevention. Their low frequency makes them time consuming to study. AIM: To conduct an epidemiological study of early epileptic seizures at the acute stroke phase and to derive principles for screening, diagnosis and behavior for prevention. CONTINGENT AND DESIGN: To achieve the goal we`ve researched retrospective patients, totally amounting to 656. RESULTS AND DISCUSSION: The factors identified so far in the genesis of seizures such as age, type and location of cerebrovascular accident and proximity to the cortex do not act alone, but in combination with undiscovered ones. CONCLUSIONS: There are no clear criteria to outline the rules for the AED prophylactic in patients with cerebrovascular disease (CVD). The most important indicator is the systematic assessment of the risk of seizures in the course of the disease. Patients at high risk of triggering seizures and developing epilepsy in CVDs are suitable for EEG examinations with a view to timely diagnosis and treatment.